2015
DOI: 10.1007/s11207-015-0796-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Umbral Dots with the New Vacuum Solar Telescope

Abstract: Umbral dots (UDs) are small isolated brightenings observed in sunspot umbrae. They are convective phenomena existing inside umbrae. UDs are usually divided into central UDs (CUDs) and peripheral UDs (PUDs) according to their positions inside an umbra. Our purpose is to investigate UD properties and analyze their relationships, and further to find whether or not the properties depend on umbral magnetic field strengths. Thus, we selected high-resolution TiO images of four active regions (ARs) taken under the bes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
1
16
2
Order By: Relevance
“…The scatter plot derived from PLGs shows a distribution similar to that found by Berrilli et al (2002) and Yu et al (2011) in their studies on quiet-Sun granulation. Indeed, the UDs distribution revealed from our study is not in agreement with the results found by Kilcik et al (2012) and Ji et al (2016). The LBGs distribution is similar to the UDs distribution, although for LBGs the range of intensity values is shifted into higher intensities.…”
Section: Resultscontrasting
confidence: 96%
See 3 more Smart Citations
“…The scatter plot derived from PLGs shows a distribution similar to that found by Berrilli et al (2002) and Yu et al (2011) in their studies on quiet-Sun granulation. Indeed, the UDs distribution revealed from our study is not in agreement with the results found by Kilcik et al (2012) and Ji et al (2016). The LBGs distribution is similar to the UDs distribution, although for LBGs the range of intensity values is shifted into higher intensities.…”
Section: Resultscontrasting
confidence: 96%
“…Other authors studied the mean UDs intensity referring to the adjacent umbral background. The UDs mean intensity obtained by Watanabe et al (2012) is 1.46-1.50 I ud /I bg , where I ud is the maximum umbral dot intensity and I bg is the adjacent umbral background, while the results obtained by Ji et al (2016) indicate that the UDs intensity is in the range between 1.05 I ud /I bg and 1.15 I ud /I bg . Among the physical properties, the study of Doppler velocities inside UDs was carried out by several authors.…”
Section: Individual Featuresmentioning
confidence: 84%
See 2 more Smart Citations
“…Then, we co-aligned the SDO and NVST images using the subpixel registration algorithm, respectively (Feng et al 2012;Yang et al 2014;Ji et al 2015). Because 304Å and Hα images have similar structures, we used a cross-correlation method to align the two images and then the other wavelength images of AIA were co-aligned with the 304Å images.…”
Section: Observations and Methodsmentioning
confidence: 99%